THE IMPACT OF PRENATAL YOGA ON HIP PAIN AMONG THIRD-TRIMESTER PREGNANT WOMEN: A RANDOMIZED CONTROLLED TRIAL - Chairiyah, Royani; Yuria R.A, Mella; Randayani Lubis, Dinni (JURNAL KESEHATAN REPRODUKSI, 2025)
Background: Hip pain is a common musculoskeletal complaint during pregnancy and may reduce mobility and quality of life. Safe and effective non-pharmacological interventions are therefore needed. Prenatal yoga is commonly recommended to enhance physical comfort and well-being during pregnancy. Objective: To assess the effectiveness of prenatal yoga in reducing hip pain among pregnant women. Method: A randomized controlled trial was conducted at an independent midwifery practice from July to December 2023. A total of 240 pregnant women were randomly assigned to an intervention group (n = 120) and a control group (n = 120). The intervention group attended prenatal yoga sessions led by a certified instructor twice weekly for four weeks, with each session lasting 60 minutes. The control group received standard antenatal care only. Hip pain intensity was measured using the Visual Analogue Scale (VAS) before and after the intervention. Data were analyzed using the Wilcoxon, Mann–Whitney, and chi-square tests. Results: The prenatal yoga group showed a significantly greater reduction in hip pain compared to the control group (p = 0.030). Pain resolution occurred in 78.2% of the intervention group and 8.3% of controls (RR = 1.279). Conclusion: Prenatal yoga is effective in reducing hip pain among pregnant women.